Sulh as an instrument of Alternative Dispute Resolution (ADR): practice in syariah court of Negeri Sembilan - Suhaizad Saifuddin; Nurul Fadhlina Che Daud; Nurul Akmar Mohamad Hilmi (Penerbit Universiti Kebangsaan Malaysia, 2024)
Sulh is one of the Alternative Dispute Resolution (ADR) mechanisms recommended by Islam. This mechanism has been implemented through Majlis Sulh establishment, which was first introduced in the year 2000 in several Syariah Courts in Malaysia and later implemented in Syariah Court of Negeri Sembilan a few years after. Throughout its implementation, Sulh has successfully resolved many cases out of court without requiring lengthy time or costs. However, Majlis Sulh are not without challenges in assisting parties to resolve disputes without litigation. This writing aims to analyze te implementation of Sulh in the Syariah Court of Negeri Sembilan and propose appropriate suggestions to enhance the effectiveness of Sulh towards optimal achievement. This study applies a qualitative research framework. Primary and secondary data were obtained through library research and documentation. Besides that, data were obtained through interviews with three Sulh officers serving in the Syariah Court of Negeri Sembilan. All data were analysed using content analysis methods. The study shows that Sulh implementation through the Majlis Sulh in this state has successfully achieved the outlined objectives and positive level. However, several challenges have been identified in its implementation. To ensure the successful momentum in case resolution is maintained, several suggestions are proposed to ensure the implementation of Sulh maintains as an effective mechanism for Alternative Dispute Resolution in the Syariah Court of Negeri Sembilan in the future.